2020
DOI: 10.1111/cas.14706
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil prognostic scores for patients with head and neck squamous cell carcinoma treated with nivolumab

Abstract: Although nivolumab, a programmed cell death 1 (PD-1) inhibitor, is a standard therapy for platinum-refractory recurrent or metastatic head and neck squamous cell carcinoma (R/M HNSCC), no definitive biomarkers have been reported thus far. This study aimed to select promising prognostic markers in nivolumab therapy and to create a novel prognostic scoring system. In this retrospective cohort study, we reviewed patients with R/M HNSCC who were treated with nivolumab from April 2017 to April 2019. We developed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…Consistent with our results, Nishikawa et al demonstrated that higher eosinophil counts and increases were associated with better survival 13,18 . Furthermore, eosinophil accumulation was associated with better survival in patients with melanoma treated with ICI 19 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with our results, Nishikawa et al demonstrated that higher eosinophil counts and increases were associated with better survival 13,18 . Furthermore, eosinophil accumulation was associated with better survival in patients with melanoma treated with ICI 19 .…”
Section: Discussionsupporting
confidence: 93%
“…To date, several studies have reported the association of patient-related factors, including the best overall response (BOR), the occurrence of immune-related adverse events (irAEs), programmed death-ligand 1 (PD-L1) expression, high mutational burden, hematological in ammatory, and nutritional markers, and clinical outcomes in RM-HNC patients treated with nivolumab therapy [5][6][7][8][9][10][11][12][13] . However, the optimal prognostic factors for nivolumab therapy in patients with RM-HNC are controversial.…”
Section: Introductionmentioning
confidence: 99%
“…Nivolumab, a programmed cell death 1 (PD-1) inhibitor, was approved in 2017 to treat platinum-refractory recurrent or metastatic head and neck cancer (RM-HNC) in Japan, receiving the results of CheckMate 141 trial 1 . Although nivolumab is highly effective in some patients, more than half of these patients do not have clinical benefits.To date, several studies have reported the association of patient-related factors, including the best overall response (BOR), the occurrence of immune-related adverse events (irAEs), programmed death-ligand 1 (PD-L1) expression, high mutational burden, hematological inflammatory, and nutritional markers, and clinical outcomes in RM-HNC patients treated with nivolumab therapy [5][6][7][8][9][10][11][12][13] . Although several studies reported the utility of the combination of these factors in ICIs therapy, we found only one study in head and neck caner [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…To date, several studies have reported the association of patient-related factors, including the best overall response (BOR), the occurrence of immune-related adverse events (irAEs), programmed death-ligand 1 (PD-L1) expression, high mutational burden, hematological inflammatory, and nutritional markers, and clinical outcomes in RM-HNC patients treated with nivolumab therapy [5][6][7][8][9][10][11][12][13] . Although several studies reported the utility of the combination of these factors in ICIs therapy, we found only one study in head and neck caner [13][14][15][16][17] . Therefore, the optimal prognostic factors for nivolumab therapy in patients with RM-HNC are still controversial.…”
mentioning
confidence: 99%
“…Our study reports, for the first time, the prognostic role of this peripheral cells in advanced HCC patients treated with IT. The prognostic role of eosinophils in patients treated with IT was already described in other neoplasms [50][51][52]. Evidence exists that the TME can be regulated by eosinophils and neutrophils [52,53], possibly underlying their prognostic role in patients treated with IT.…”
Section: Discussionmentioning
confidence: 74%